ANALISIS FAKTOR-FAKTOR PENENTU KINERJA KARYAWAN BUMDes DI KABUPATEN JEMBRANA - Swandari, Ni Komang Ayu Sri; Setiawina, Nyoman Djinar; Marhaeni, A.A. I.N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.04.TAHUN 2017, 2017)
One of them is the low performance of employees village-owned enterprises. The low performance of employees can be seen from the low level of employee discipline and the work produced is not maximized. Methods of data collection are observation, questionnaire and deep interview. The analysis showed that : 1) the village-owned enterprises were able to absorb manpower; 2) the village-owned enterprises were able to give a role to the original income of the village; 3) work experience, salary, work environment and leadership style positively and significantly impact on work motivation of employees of the village-owned enterprises, and age has negative and significant effect on employee motivation of the village-owned enterprises; 4) Work environment and motivation positively and significant effect on employee performance of the village-owned enterprises. Work experience, salary, age and leadership style does not significantly influence employee performance of the village-owned enterprises; 5) indirectly variables education through work motivation does not significantly influence employee performance BUMDes, while the variables of age, work experience, salary, work environment and leadership style indirectly significant effect on employee performance BUMDes through motivation work.
Keywords: education, work experience, age, salary, work environment, leadership style, motivation and performance